Parcs agroforestiers sahéliens : de la conservation à l’aménagement - G. Smektala; R. Peltier; N. Sibelet; M. Leroy; R. Manlay; C. F. Njiti; M. Ntoupka; A. Njiemoun; O. Palou; Tapsou (VertigO, 2005)
In North-Cameroon, as in all semi-arid regions of Africa, farmers have for a long time been clearing wooded savannah land in order to cultivate it. This clearing has often been selective, in that farmers have retained the trees that cause them least trouble and those that are useful. They sometimes enrich these agroforestry systems later by introducing new species or by conserving part of the natural regeneration. Various types of wooded parklands have been created, depending on the composition of the original tree population, the ecological conditions, the know-how and requirements of the local populations and their socio-economic environment. The most well known are the faidherbia parklands (Faidherbia albida) and the shea parklands (Vitellaria paradoxa).Between 1950 and 1990, the forestry Department had a policy to protect trees located in fields and in indigenous forests, by prohibiting the cutting of trees. Although these conservation policies were effective in preserving the parklands, they also had a counterproductive effect because farmers felt they were being deprived of the right to manage their tree heritage, with the result that they stopped conserving and planting young trees and the stands aged.Research, development and teaching activities conducted in North-Cameroon by various projects have shown that it is possible to revitalise the management of these agroforestry systems at the farm and village community level. The rights of stakeholders to exploit these trees need to be secured, and this could involve the creation of "community forests", provided for in the Cameroonian forestry law of 1994, and that could include village agroforestry parklands. If that was established, rights over the trees would be transferred from the State to the community, and the villagers would be able to exploit them within a defined management plan.In preparation for this procedure, traditional deliberate tree management practices were described: pruning method was tested that reconciles conservation with trunk development and leaf, fruit and wood production. It enabled the biomass stock of the trees and their annual production to be measured. We discuss the combinations of tree management techniques that could be applied to the parklands and put forward some suggestions for simplified models of parkland management. These strategies would enable the villagers to produce firewood (a scarce resource) through pruning, while still preserving the parklands. This approach also has the support of those in power in the forestry Department and of the research and development organisations, despite the reluctance of the local forestry officials who fear it will undermine their power and advantages.All that remains now is to implement the plan. It will require funding, which could come from the Global Environment Facility (GEF).